Quantification of ventricular repolarization heterogeneity during moxifloxacin or sotalol administration using -index. (April 2015) - Rivolta, M W; Mainardi, L T; Sassi, R
Abstract Drug-induced alterations of ventricular heterogeneity must be limited to avoid induction of lethal ventricular arrhythmias. In here, a new parameter called <?CDATA $\mathcal{V}$ ?> <?MML V ?><inline-graphic xlink:href="ark:/27927/pgj2cb2tnvq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />-index, able to measure the standard deviation of myocites' repolarization times, was evaluated after moxifloxacin and sotalol administration. The two drugs are known to provide different alteration of the QT interval length ranging from subtle (moxifloxacin) to evident (sotalol). In fact, while the former is employed as active-comparator in thorough QT studies, the latter might induce torsades de pointes. 24 h Holter ECGs of 39 (sotalol) and 68 (moxifloxacin) healthy subjects were retrospectively analyzed. The recordings were performed after infusion of the drugs and after the placebo (moxifloxacin) or at baseline (sotalol). The corrected QT interval (QTc) was included as well in the study, for a direct comparison. In both populations, <?CDATA $\mathcal{V}$ ?> <?MML V ?><inline-graphic xlink:href="ark:/27927/pgj2cb2tnmv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />-index and QTc increased along with the drugs' serum concentration and were statistically different from values in the placebo arm or at baseline (p < 0.05). With sotalol, the maximum value of <?CDATA $\mathcal{V}$ ?> <?MML V ?><inline-graphic xlink:href="ark:/27927/pgj2cb2tp56" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />-index occurred, on average, after 5.64 h from the infusion, whereas for QTc after about 4.27 h. The two metrics displayed evident changes ( <?CDATA $\mathcal{V}$ ?> <?MML V ?><inline-graphic xlink:href="ark:/27927/pgj2cb2tp33" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />-index: 27.79 ms ± 4.89 ms versus 60.13 ms ± 18.52 ms; QT corrected: 387.07 ms ± 19.84 ms versus 437.76 ± 32.05 ms; p < 0.05). Regarding moxifloxacin, maximum values were reached, on average, 5.01 h after administration for <?CDATA $\mathcal{V}$ ?> <?MML V ?><inline-graphic xlink:href="ark:/27927/pgj2cb2tn3k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />-index (30.70 ms ± 8.32 ms versus 40.48 ms ± 7.61 ms; p < 0.05), and 4.37 h for QTc (404.29 ms ± 29.05 ms versus 426.77 ± 36.67 ms; p < 0.05). They were statistically different from baseline values. With both drugs, the maximal percent variation after administration was higher for <?CDATA $\mathcal{V}$ ?> <?MML V ?><inline-graphic xlink:href="ark:/27927/pgj2cb2tp9d" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />-index than QTc (moxifloxacin: 34.56% ± 24.60% versus 5.56% ± 2.98% ; sotalol: 114.77% ± 33.15% versus 12.13% ± 2.85% ; p < 0.05). The study suggests that the standard deviation of the ventricular repolarization times, as quantified by the <?CDATA $\mathcal{V}$ ?> <?MML V ?><inline-graphic xlink:href="ark:/27927/pgj2cb2tngn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />-index, might be an effective measure of spatial heterogeneity.